Correlative FLIM-confocal-Raman mapping applied to plant lignin composition and autofluorescence. (November 2019) - Wightman, Raymond; Busse-Wicher, Marta; Dupree, Paul
Highlights: Fluorescence lifetime imaging, confocal and Raman on the same microscope/sample. Lifetime changes of lignin fluorescence correlate with Raman changes. Arabidopsis thaliana, cad2 cad6 double mutant exhibits shorter lifetimes. Loss and gain of peaks in mutant Raman spectra compared to those of wild type. Abstract: Fluorescence lifetime imaging microscopy (FLIM) is a useful tool for discriminating fluorescent moieties, based on photon lifetimes, that cannot be otherwise resolved by looking solely at their excitation/emission characteristics. We present a method for correlative FLIM-confocal-Raman imaging and its application to lignin composition studies in the woody stems of the plant model Arabidopsis thaliana . Lignin is autofluorescent and exhibits characteristic fluorescence lifetimes attributed to its composition. Its composition can be further resolved by Raman microscopy to multiple peaks that represent different components. A lignin biosynthetic mutant is found to have a marked difference in fluorescence lifetime and corresponds to a change in composition as demonstrated by the Raman output.